Roles assigned to heritage learners in beginner Spanish mixed classes - Asención-Delaney, Yuly (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Recent data indicate that there is a large population of Spanish Heritage Learners (HLs) in postsecondary institutions in the U.S. (National Center for Education Statistics [NCES], 2017).  However, only 40% of institutions offer at least one course for this student population (Beaudrie, 2012). This situation forces HLs to take language courses designed for Spanish second language learners (i.e., mixed classes). This article reports a study that was carried out to answer the following research questions: a) what roles do instructors assign to HLs in their beginner classes, and b) how do these observed roles support the HL language instruction goals and meet their needs for cultural connection?  Results indicate that teachers assign a variety of roles to heritage learners in their beginner Spanish classes. These roles include serving as a language model or informant in terms of linguistic, pragmatic or cultural knowledge, translating and tutoring.  The assigned roles could support or inhibit heritage learners’ linguistic and cultural goals depending on their linguistic level. This article concludes with a discussion of the implications of these findings as they pertain to the required teacher training to better serve these learners in mixed language classes.